GenAI-supported portfolio assessment for complex thinking: a GPT-based innovation in business education - Portuguez-Castro, May; Castillo-Martínez, Isolda Margarita (Frontiers in Education, 2026)
This study examines the integration of Generative Artificial Intelligence (GenAI) into rubric-based qualitative assessment to strengthen authentic evaluation and complex thinking competencies in business education. Conducted at a graduate business school in Peru with 120 student portfolios, the research adopted a qualitative exploratory-documentary approach, complemented by a correlational analysis between human and AI evaluations to enhance the interpretive validity of the findings. A pilot subsample (n = 12) was used for the correlational analysis comparing human and AI-assisted assessments, while descriptive analyses of complex thinking levels were conducted on the full sample (n = 120) using the AI agent. The study employed the GPT-eComplex Assistant, a GenAI-based evaluator developed from ChatGPT and configured with the eComplex rubric, to identify recurring patterns, strengths, and areas for improvement without replacing human pedagogical judgment. The findings revealed that: (a) the GPT-eComplex Assistant closely mirrored human evaluators’ judgments, reinforcing consistency, traceability, and transparency, although still requiring teacher calibration; (b) the digital portfolio served as an authentic learning artifact to capture systemic and critical thinking, while showing limitations in the scientific dimension; (c) the use of GenAI for assessment in higher education remains incipient and under-researched, underscoring the need for empirical evidence and ethical guidelines; and (d) the responsible integration of GenAI demands active teacher mediation, ethical awareness, and institutional transparency, ensuring that technology complements rather than replaces pedagogical judgment. This study contributes a pedagogical strategy that combines formative portfolio assessment, AI-supported co-evaluation, and the AI-PROMPT Framework, offering a replicable model for embedding GenAI into authentic, reflective, and ethically grounded assessment practices in higher education. The results represent an innovative contribution by positioning GPT as a complementary tool in authentic assessment, reinforcing the central role of human judgment and opening new perspectives for AI-supported evaluation in the Ibero-American and beyond.